THU0476 Spontaneous vertebral fracturesafter denosumab discontinuation: a report of 6 cases. (12th June 2018) - Florez, H.; Ramírez, J.; Monegal, A.; Guañabens, N.; Peris, P.
Abstract : Background: Denosumab (Dmab) is an antiresorptive treatment with demonstrated efficacy in osteoporosis. However, discontinuation of Dmab has been associated with rapid bone loss, and recently, the development of vertebral fractures (VF) in some patients. It is essential to identify the risk factors for these adverse events and follow its evolution. Objectives: To analyse the clinical characteristics, parameters of bone metabolism and evolution of patients developing VF after Dmab discontinuation. Methods: Six women with spontaneous VF after Dmab discontinuation were included (median age 66 years 56–75 ). The clinical history, cause of osteoporosis, treatments received, fractures, Dmab treatment duration and discontinuation period were reviewed. Additionally, the clinical and densitometric evolution, and bone mineral parameters were also analysed after Dmab discontinuation. Results: All the patients had postmenopausal osteoporosis, and one was receiving glucocorticoid treatment; 3/6 patients had previous fractures (2 VF and 1 calcaneus); 4/6 had previously received antiosteoporotic treatment (hormone replacement therapy, risedronate, alendronate, zoledronate [once or consecutively)] during 1–23 years. All had received Dmab for 24–53 months (median 37). The reasons for treatment discontinuation were: dental indication (1 patient), BMD improvement (T-score −1.2) (1 patient), poor adherence, 1 prescription problems and/or delay in administration. 3 The median bone mineral density T-scores prior to VF were −2.6 (-1.2/–4) at the lumbar spine and −3.0 (-0.6/–3.7) at the femoral neck. The mean time between the last Dmab dose and VF was 9.5 months, 8–20 with a median of 5 VFs/patient. 2–8 No patient showed 25-OH vitamin D<20 ng/ml. After Dmab discontinuation, bone turnover markers increased (median increase +364% in PINP and +287% in NTx); one patient presented hypercalcaemia (Ca 11.3 mg/dL); and BMD decreased 1%–21% in the lumbar spine and 2%–6% in total hip at 8–19 months. After VF, 3 patients restarted Dmab, 1 received zoledronate and 2 alendronate. No new fractures occurred during follow-up. Conclusions: Discontinuation of Dmab is associated with an increase in bone turnover markers and bone loss which can be associated with the development of spontaneous VF. Previous bisphosphonate therapy does not seem to decrease this risk. Further studies are needed to assess the optimal antiresorptive treatment and its duration after Dmab discontinuation. Disclosure of Interest: None declared